1970
DOI: 10.1002/1097-0142(197008)26:2<279::aid-cncr2820260206>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte transformation in malignant lymphomas

Abstract: Peripheral blood leukocyte cultures with phytohemagglutinin (PHA) were studied in 19 patients with malignant lymphomas, classified as Stage IV. Thirteen patients had lymphosarcoma and 6 had reticulum cell sarcoma. Control subjects included both healthy and chronically ill subjects. Seventeen patients with Hodgkin's disease were also studied. A wide range of responsiveness to PHA was observed in cases of lymphosarcoma with a median value for the group lower than that of control subjects. Correlation of lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The absolute number of these nonresponsive cells was increased in 2 FLL cases. Similar results have been obtained in patients with well-differentiated lymphocytic lymphomas (Quaglino and Cowling, 1964;Lawler et al, 1968;Rubin et al, 1969;Papac, 1970;Liknaitzky et al, 1970). These cells appear to be analogous to the non-transforming cells of CLL.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The absolute number of these nonresponsive cells was increased in 2 FLL cases. Similar results have been obtained in patients with well-differentiated lymphocytic lymphomas (Quaglino and Cowling, 1964;Lawler et al, 1968;Rubin et al, 1969;Papac, 1970;Liknaitzky et al, 1970). These cells appear to be analogous to the non-transforming cells of CLL.…”
Section: Discussionsupporting
confidence: 79%
“…The data of Rubin et al (1969) suggest that they do so in 5 or 6 days, thus also supporting the concept that the abnormal CLL cells correspond in the normal with the PHA-responsive population of lymphocytes. However, this view is not supported by the findings of Wilson and Nossal (1971) and those of Papamichail et al (1971), who have demonstrated immunoglobulins on the surface of CLL lymphocytes which resembled the findings in the B-lymphocytes. Thus, the question of the B or T nature of these cells is still open (Catovsky and Holt, 1971).…”
Section: Discussionmentioning
confidence: 71%
“…The immunologic defect of early active HD is characterized by depression of delayed hypersensitivity and decreased homograft reactions (2,3). Antibody formation is largely intact and peripheral lymphocyte counts are normal or slightly decreased, while a loss of phytohemagglutinin (PHA) responsiveness of lymphocytes in HD has been reported even before peripheral lymphocyte depletion has occurred (4). Thus a defect of T-lymphocyte reactivity is well established, but its role in the pathogenesis of the disease itself is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…WHILST depression of the PHA response in chronic lymphatic leukaemia (Smith, Cowling and Barker, 1972), Hodgkin's disease (Trubowitz, Masek and Del Rosario, 1966) and other malignant lymphomata (Papac, 1970) is now well established, the change in non-lymphoid malignancies remains in doubt. Most reports indicate that a similar depression occurs in the non-lymphoid malignancies (Silk, 1967;Ducos et al, 1970;Whittaker, Rees and Clark, 1970;Hann and Takita, 1972) but there are conflicting data indicating that the response may be normal (Robinson and Hurvitz, 1966;Sutherland, Inch and McCredie, 1971;Nelson, 1969).…”
mentioning
confidence: 99%